Effect of Propolis on the Adhesion Index, Morphology and Viability of Candida albicans Cells on Biofilm Formation - Dinda Oktia Maghfiroh; A.A. Santi Dewi; Anggie Diniayuningrum; Bambang Rahardjo; Nurdiana Nurdiana; Agustina Tri Endharti; Sumarno Sumarno (Medical Laboratory Technology Journal, 2021)
Approximately 70-75% of reproductive women have experienced vulvovaginal candidiasis at least once, and 40-45% will have recurrences. Candida albicans is the most etiology of vulvovaginal candidiasis and is able to form a biofilm that can lead to antifungal resistances and recurrences. One of the natural products that have an anti biofilm effect is propolis. This study expected that propolis from Lawang can be one of the anti-biofilm agent candidates for antifungal resistant cases. This study aimed to know the anti-biofilm effect of propolis ethanol extract on cell adhesion index, morphology, and viability of Candida albicans cell on biofilm formation. The adhesion index was counted on 100 epithelial cells under light microscopy (1000x). Morphology was seen using light microscopy (400x). Cell viability was examined by CFU assay. At 12.5% concentration of propolis ethanol extract, adhesion index decreased (p=0,000), and hyphal growth was inhibited. Colony growth decreased at 2.5% concentration and was not seen at 10% concentration of propolis ethanol extract (p=0,000). These results indicated that propolis ethanol extract could decrease adhesion index, failed the Candida albicans morphology transition from yeast to hyphal, and decreased Candida albicans cell viability on biofilm formation. Propolis ethanol extract is likely to be one of the alternatives to recurrent vulvovaginal candidiasis treatment, especially caused by Candida albicans biofilm formation.